Investigating the Impacts of Ionospheric Irregularities on Precise Point Positioning Over China and Its Mechanism - Wei Li; Shuli Song; Weili Zhou; Na Cheng; Chao Yu (Space Weather)
Abstract The impacts of ionospheric irregularities on precise point positioning (PPP) have been commonly noticed in the field of the ionosphere and the precise application of the Global Navigation Satellite System. But few attentions have been paid to how ionospheric irregularities deteriorate the performance of PPP. Aiming at exploring the mechanism of degradation of PPP solutions during the period of ionospheric irregularities, this paper investigates the impacts of ionospheric irregularities on the performance of kinematic PPP. The experiment uses GPS observation data sampled at the 30‐s interval over China on the days of 2014, 2015, and 2017 covering some active space weather, for example, solar and geomagnetic activities. The results show that the ionospheric irregularities caused increased positioning errors (decimeter‐ to meter‐level), enlarged phase residuals (decimeter‐level), and increased the number of detected cycle slips in PPP processing in low latitude regions of China. By proposing a novel strategy that compares the number of detected cycle slips from 30 s‐sampling interval data and 1s‐sampling interval data at the same station in an “aligned” mode, we present direct evidence of the existence of the falsely detected cycle slips in 30 s‐sampling interval data by the traditional cycle‐slip detection threshold in PPP processing. We reveal that the unnecessary and frequent reinitialization of ambiguity induced by the falsely detected cycle slips is dominantly responsible for the degradation of kinematic PPP solutions during the period of ionospheric irregularities. Our findings pointed out the direction for the improvement of kinematic PPP performance in the environment of ionospheric irregularities.